Diffuse optical tomography : principles and applications - Jiang, Huabei (Boca Raton, FL. : CRC Press, 2011)
'Based on near infrared optical technologies and model-based inverse computations, DOT is an imaging method that can provide spatial distributions of intrinsic tissue optical properties through model-based reconstruction algorithms using NIR measurements along or near the boundary of tissue. This book covers almost every aspect of DOT--from mathematics, reconstruction algorithms, instrumentation, and phantom experiments to clinical applications. The text covers the fundamentals principles of DOT, including its mathematical foundations and computational methods, and explains how to set up experimental image systems, as well as how to translate laboratory studies into clinical applications'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Optical tomography